It's being done in social studies : race, class, gender and sexuality in the pre/K-12 curriculum - Willox, Lara; Brant, Cathy (International social studies forum, the series., 2019)
"After our recent CUFA conference, many social studies teacher educators came to realize that pre-service teachers are skeptical of calls to integrate sensitive topics in the curriculum because they do not see it in their field experiences. The purpose of this edited book is to share examples of Pre/K - 12 grade teachers, schools, or school systems that infuse race, class, gender and sexuality in the curriculum. This book offers concrete examples of social studies teachers, schools and schools systems committed to the inclusion of topics often deemed as sensitive or controversial. Care was taken to provide examples from diverse geographic areas, school types (public, charter, private etc.), and grade levels. Researchers teamed with practicing professionals to highlight teachers and schools that successfully integrate race, class, gender and/or sexuality in the curriculum. The chapters provide specific examples of content inclusion, share high leverage practices, and provide advice for others infusing race, class, gender, and sexuality in the curriculum"--